2021
DOI: 10.1177/11786221211042381
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Soil Cation Exchange Capacity in Entisols with Divergent Textural Classes: The Case of Northern Sudan Soils

Abstract: Cation exchange capacity (CEC) is an important soil property because it affects the assimilation of nutrients and buffers against soil acidification. Thus, knowledge of CEC is considered key to developing agricultural and environmental models for land management planning. However, in developing countries such as Sudan, there is a lack of soil CEC data due to the absence of research projects and funding to develop this information. Therefore, this research was conducted to predict CEC for large areas using spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 74 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…SCEC is the ability of soil to store nutrients such as NH₄⁺, H, Ca, Mg, K, and Na [ 28 , 29 ]. The SCEC test result indicates 23.16 meq/100 g soil from samples tested as an average.…”
Section: Resultsmentioning
confidence: 99%
“…SCEC is the ability of soil to store nutrients such as NH₄⁺, H, Ca, Mg, K, and Na [ 28 , 29 ]. The SCEC test result indicates 23.16 meq/100 g soil from samples tested as an average.…”
Section: Resultsmentioning
confidence: 99%
“…Obtaining information on cation exchange capacity is becoming increasingly important on dry land as this suffers from many problems such as lack of sufficient water to support plant growth and land degradation (Adam et al 2021). Spatio-temporal mapping of soil salinization results showed that agricultural land of Maisky District, closer to the Irtysh River, using flood irrigation, has increased CEC content.…”
Section: Resultsmentioning
confidence: 99%
“…The decline in SOM and the accumulation of excess sodium ions can negatively impact soil productivity, highlighting the need for soil conservation and restoration efforts (Olorunfemi et al, 2018). Providing a soil buffer against acidification influences how soil holds onto essential nutrients (Adam et al, 2021). The CEC tends to be higher in soils with higher clay fractions.…”
Section: Discussionmentioning
confidence: 99%